Horizontal and Vertical Firm Networks, Corporate Performance and Product Market Competition - Oliver Bischoff; Achim Buchwald (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper sheds new light on the assessment of firm networks via multiple directorships in terms of corporate firm performance. Using a large sample of European listed firms in the period from 2003 to 2011 and system GMM we find a significant compensation effect on corporate firm performance for the initial negative effect of horizontal multiple directorships by product market competition. In markets with effective competition, horizontal multiple directorships turn out to be an efficient mechanism to increase firm performance and thus assure competitive advantages. By contrast, linkages between up- and downstream firms have no significant influence on financial performance, irrespective of the level of competition intensity.
Keywords: C23; G32; G34; L14; L25; L40; 330; Horizontal and Vertical Firm Networks; Multiple Directorships; Corporate Governance; Product Market Competition; Dynamic Panel